Common variants near CAV1 and CAV2 are associated with primary open-angle glaucoma in Caucasians from the USA - Wiggs, Janey L. (Oxford University Press, 2011)
Primary open-angle glaucoma (POAG) is a genetically complex common disease characterized by progressive optic nerve degeneration that results in irreversible blindness. Recently, a genome-wide association study (GWAS) for POAG in an Icelandic population identified significant associations with single nucleotide polymorphisms (SNPs) between the CAV1 and CAV2 genes on chromosome 7q31. In this study, we confirm that the identified SNPs are associated with POAG in our Caucasian US population and that specific haplotypes located in the CAV1/CAV2 intergenic region are associated with the disease. We also present data suggesting that associations with several CAV1/CAV2 SNPs are significant mostly in women.